Non-operative approaches to major blunt hepatic (Grade IV): a case report - Amirreza Salehi; Mansoor Kodori; Mohammad Sohrabi (Journal of Medical Case Reports)
Abstract Background Recent advancements in the management of pediatric liver trauma have highlighted the effectiveness of non-operative management as the preferred therapeutic approach. This report presents the case of an 8-year-old patient who sustained significant liver trauma from a substantial fall, successfully managed through non-operative management. Case presentation An 8-year-old Iranian child presented with a Grade IV liver laceration and contusion, pneumothorax, and rib fractures after a 1.5 m fall. Initial stable vitals were confirmed. Diagnostic evaluations included serial focused assessment with sonography for trauma scans and computed tomography imaging of the thorax, abdomen, and pelvis. Treatment involved intensive care unit monitoring, intravenous fluid therapy, and a chest tube insertion. The patient’s condition improved significantly after 6 days in the intensive care unit, demonstrating the efficacy of non-operative management. The patient was successfully discharged following conservative management. Written informed consent was obtained from the patient’s legal guardian for publication of this case report and any accompanying images. Conclusions This case highlights the effectiveness of non-operative management in managing high-grade liver injuries. Over the past 2 decades, non-operative management has become increasingly prevalent, particularly in urban healthcare settings, due to its ability to manage hepatic trauma without surgical risks. Advanced imaging and multidisciplinary approaches are critical to its success.